Fish species composition and size structure exploited by gill net fishery in The New Calabar River, Nigeria - Olopade, Olaniyi Alaba; Dienye, Henry Eyina; Oderhohwo, Ogheneforon (Acta Aquatica: Aquatic Sciences Journal, 2019)
The purpose of this study was to investigate the species composition and size selectivity of gillnets commonly used by the artisanal fishers in the New Calabar River, Rivers State, Nigeria. The data was collected during February-July 2018 from 3 sampling stations: SI Choba, S2 Ogbogoro, and S3 Iwofe all along the stretch of the river. Twenty-eight fish species were found belonging to 15 families. The prevalent families were Cichlidae, Mugilidae and Clupeidae representing 32.22%, 30.36% and 10.23% of the total catch, respectively. The most dominant species in terms of number were Liza falcipinnis (12.58%) and Mugil cephalous (12.26%) while in terms of biomass, the most abundance species were Xenomystus nigri (24.12%) and Lutjanus agennes (12.50 %). The girth and total lengths of the fishes ranged from 5.20±0.20 to 21.00±0.00 cm and 8.85±0.15 to 28.19±1.13 cm respectively. The length at first capture (L50%) for the most abundant species (Liza falcipinnis) was calculated to be 14.13 cm while that of L25% and L75% were 12.70cm and 15.25cm respectively. It was concluded that the gill nets used in the New Calabar River exploit fish species of small sizes and few medium sized specimens relative to species potential maximum size. It is therefore recommended that for an improved and sustainable exploitation fish stock of the New Calabar River, the use of gillnets of less than 25 mm-mesh sizes and other gears should be prohibited.Keywords: gill nets; species composition; mesh size; selectivity; New Calabar River